The relative anthelmintic efficacy of plant-derived cysteine proteinases on intestinal nematodes - Luoga, W; Mansur, F; Buttle, DJ; Duce, IR; Garnett, MC; Lowe, A; Behnke, JM (Cambridge Univ Press, 2024)
Indexed by Scopus/WOS